Reducing the carbon footprint when using non-metallic minerals as litter in poultry farms - Natalia Sannikova; Olga Kovaleva; Olga Shulepova; Anna Bocharova; Vladimir Melnikov (Revista Ingeniería UC, 2022)
Poultry farming is one of the most eﬃcient and dynamic branches of animal husbandry. The advantages of the poultry industry are lower prices compared to other types of meat and its high quality (white meat with low-fat and high protein content). The article presents the results of industrial and experimental studies on using a cellulose-containing natural component (diatomite) as part of litter material in poultry farms to improve sanitary conditions and reduce the negative impact on the environment. Experiment study was chosen as the main research method. The research was carried out on the territory of a poultry enterprise with a total population of 24.000 heads. The authors conclude that using a cellulose-containing natural component (modiﬁed diatomite) as part of the litter material in poultry farms allowed to reduce emissions of pollutants, thereby reducing the greenhouse eﬀect at the level of one poultry farm.